Development of Online SABASIA (Suka Bahasa Indonesia) Teaching Materials for Indonesian Language Learning for International Students as a Pioneer for FIBAA International Accredited Study Programs at State Islamic Universities - Sri Nugraheni, Aninditya; Lestari, Shindy; Husain, Alma Pratiwi; Susanto, Eri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
Teaching materials are needed to implement learning: the Indonesian Language for Foreign Speakers (BIPA). BIPA learning is one of the facilities for international students to learn Indonesian; besides, it is also used as a pilot program for International Accreditation at a university; in its journey, it requires innovation of teaching materials to support the BIPA learning process. This study aims to determine the feasibility and effectiveness of online SABASIA (Suka Bahasa Indonesia) teaching materials in Indonesian language learning for international students as a pioneer of the FIBAA Accredited Study Program at State Islamic Universities. This research is a type of research and development (RnD). The research data were obtained using observation, discussion with experts, interviews, and questionnaires. The results showed 1) at the online SABASIA (Suka Bahasa Indonesia) teaching material innovation stage, international students received a positive response, with 79% of international students at State Islamic universities in dire need of innovative teaching materials. The quality of developing SABASIA (Suka Bahasa Indonesia) Online teaching materials is done by validating the experts and then getting product revisions. It was found that online SABASIA (Suka Bahasa Indonesia) teaching materials are acceptable and appropriate for international students to use in helping to deepen the Indonesian language, especially in State Islamic Universities. 2) the effectiveness of online SABASIA (Suka Bahasa Indonesia) teaching materials In Indonesian language learning for international students at state Islamic Universities, the results of the pre-test and post-test have increased so that they are declared effective and can be used as pioneering FIBAA internationally accredited study programs in universities, State Islam. The development of online SABASIA (Suka Bahasa Indonesia) teaching materials is an innovation in learning Indonesian using information and communication technology, based on bilingual.